Non-financial reporting: identifying the role of accounting through bibliometric analysis - Krawczyk, Patrycja (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The subject of financial reporting has been discussed for decades. The concept of non-financial reporting (NFR) arose later, and thus the study of this field began slightly later. This is currently a subject with great research potential. Both the multitude of studies of the scientific community and data obtained from business practice confirm the increase in the importance of non-financial reporting. A review of publications on this subject will indicate the state of this area of research. Particular attention will be paid to the role of NFR from an accounting point of view. Aim: Evaluation of non-financial reporting as a new area of scientific research using bibliometric analysis of scientific publications indexed in the Web of Science database. Investigating the contribution of scientific communities related to accounting, in the development of this area of research. Results: The results will allow for assessing the research activity and the stage of development of the research in the field of non-financial reporting. What is the level of interest of accounting-related scientists in this subject? The latest correctly conducted scan of the issue of NFR will reliably summaries the current state of knowledge, providing information about gaps in the literature and the need to carry out new research. It can also be a way to identify new research areas. The bibliometric analysis of non-financial reporting from the accounting point of view will be a new and original contribution to research in this field.